2010
DOI: 10.1074/jbc.m110.177402
|View full text |Cite
|
Sign up to set email alerts
|

Local Sequence Targeting in the AID/APOBEC Family Differentially Impacts Retroviral Restriction and Antibody Diversification

Abstract: Nucleic acid cytidine deaminases of the activation-induced deaminase (AID)/APOBEC family are critical players in active and innate immune responses, playing roles as target-directed, purposeful mutators. AID specifically deaminates the host immunoglobulin (Ig) locus to evolve antibody specificity, whereas its close relative, APOBEC3G (A3G), lethally mutates the genomes of retroviral pathogens such as HIV. Understanding the basis for the target-specific action of these enzymes is essential, as mistargeting pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 53 publications
(39 reference statements)
8
75
0
Order By: Relevance
“…Previous studies have demonstrated the importance of loop 7 residues in sequence selectivity of related A3 family members, AID, A3A, A3F, and A3G (53,(55)(56)(57)(58). Consistent with these reports, replacing loop 7 of A3B with that from A3G (GL7) converted the target sequence preference to 5Ј-CC-3Ј preferred by A3G (cytosine 1691 in rpoB; Fig.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Previous studies have demonstrated the importance of loop 7 residues in sequence selectivity of related A3 family members, AID, A3A, A3F, and A3G (53,(55)(56)(57)(58). Consistent with these reports, replacing loop 7 of A3B with that from A3G (GL7) converted the target sequence preference to 5Ј-CC-3Ј preferred by A3G (cytosine 1691 in rpoB; Fig.…”
Section: Resultssupporting
confidence: 74%
“…Previous structural and functional studies of A3 proteins have demonstrated that loop 1 (between ␣1 and ␤1) and loop 7 (between ␤4 and ␣4) surround the active site and suggested that these flexible regions play important roles in binding singlestranded DNA substrates (30,53,(55)(56)(57)(58). The structures of A3Bctd-QM⌬loop3 in both crystal forms show a tightly closed conformation of the active site compared with those observed for other A3 proteins (Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…HIV-1 hypermutated genomes show mutational hot spots as well, which are due to preference of A3G and A3F for deamination of the third C in 5’-CCC (negative-strand) and 5’-GGC, respectively 51, 52 . The context of the C complementary to G181 (5’-GGC) differs from what has been described for APOBEC3, suggesting that if At CDAs had context preference, it would be different from the one described for A3G.…”
Section: Discussionmentioning
confidence: 99%
“…31 In conjunction with other studies, this work established the role of loops 1, 3 and 7 in the process of DNA substrate recognition. 24,[31][32][33][34][35] Initial crystal structures of A3 deaminase domains show these loops being adjacent to the binding site. 22 Subsequent crystallization of A3 proteins in complex with substrates showed residues on loops 1 and 7 binding to oligonucleotide substrates.…”
Section: Introductionmentioning
confidence: 99%